The Effect of Flood on Water Quality from Well Water Used in Kampong Bongor, Pasir Mas, Kelantan - Ghazali, Adam; MOHD ARIF BIN ROSLI, (Progress in Engineering Application and Technology, 2025)
This study examines the effect of floods on the quality of well water in Kampong Bongor, Pasir Mas, Kelantan, with an emphasis on compliance with the Interim National Water Quality Standard Malaysia (INWQS). The analysis focused on seven water quality parameters: Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), pH, Ammoniacal Nitrogen (AN), Dissolved Oxygen (DO), Total Suspended Solids (TSS), and Total Hardness (TH). The findings revealed significant flood-induced contamination, with BOD (13.9 mg/L) and AN (6.53 mg/L) exceeding Class V thresholds, classifying the water as highly polluted. Other parameters, such as COD (32 mg/L) and TSS (34 mg/L), also indicated moderate pollution levels. In contrast, DO (7.87 mg/L) and TH (36.3 mg/L) were within Class I limits, reflecting localized variations in contamination levels. The study highlights the severe impact of flooding on well water, necessitating urgent water treatment and flood management strategies. Regular monitoring, community-based water treatment systems, and enhanced well infrastructure are recommended to mitigate health risks and safeguard water resources. These findings contribute valuable insights into the relationship between floods and water quality, offering a robust foundation for informed water management practices in flood prone rural areas.